Outcomes Following Supracoronary Ascending Aortic Replacement with Aortic Valve Resuspension versus Modified Bentall's Operation for Acute Type A Aortic Dissection - Mohammed,Sameer (2022)
Abstract Introduction: Type A acute aortic dissection (AAD) remains a challenging cardiac emergency despite the availability of various management strategies. This study compared the outcomes of supracoronary ascending aortic replacement (SCAAR) with aortic valve (AV) resuspension with those of modified Bentall's operation for type A AAD and the progression of aortic regurgitation (AR), long-term dilatation of aortic root and proximal arch, and long-term mortality in SCAAR patients. Methods: Sixty patients underwent surgery for type A AAD (January 2005 to December 2015). Forty-three patients underwent SCAAR with AV resuspension and 17 underwent modified Bentall's operation. All patients were followed up. Results: Upon follow-up of SCAAR patients (n=40), there was significant reduction in aortic root size (preoperative 39.3 mm [9.4] vs. postoperative 33.1 mm [9.1]; P<0.001). Three of these patients worsened to severe AR while others had similar or lesser degree of AR. On comparison between preoperative and postoperative dimensions of all patients (n=53), there was no significant difference in distal ascending aorta size (35.7 mm [8.1] vs. 34.4 mm [8.9]; P=0.52). However, an increase in descending thoracic aorta size (28.8 mm [7.8] vs. 33.7 mm [9.9]; P<0.001) was observed. In-hospital and late mortalities for SCAAR vs. modified Bentall's procedure were 11.7% (seven patients) (7% [3] vs. 23.5% [4]) and 28% (15 patients) (15% [6] vs. 69% [9]), respectively. Conclusion: SCAAR with AV resuspension is a safe surgical option for type A AAD. Preservation of AV is associated with better long-term outcomes and reduced mortality. Modified Bentall's operation may be associated with long-term mortality.